The nurse's role in the care of Diabetes mellitus I in the juvenile phase (Research, Society and Development, 2022)
The study aims to analyze the importance of nursing care in children with Diabetes Mellitus I, with the main purpose of emphasizing the importance of nursing professionals, taking into account that because they are on the front line of health care, nursing professionals are responsible for guidance and actions that preserve the quality of life of patients. The research carried out for the elaboration of this work can be classified, in terms of its nature as basic research, as it seeks to generate new knowledge about the actions carried out by nursing professionals in relation to patients with Diabetes Mellitus I. exploratory and qualitative nature, having been carried out a search of Most of the works that will be used were found in virtual databases, academic google platform and SciELO. The research will use as a theoretical basis, various authors who point out about the importance of nursing care for the care of children with Diabetes Mellitus I. Therefore, it was possible to verify that there are numerous issues to be faced by those who are diagnosed in the infant-juvenile stage, because this is already a complicated phase in life, in itself, and nursing care is of paramount importance, in a humanized and instructive way, since it is the professionals who will have the most contact with the patient and family during treatment. Thus, the role of nursing goes beyond administering medications, as they are an anchor that assists in the acceptance of the disease and treatment.